Complete Defect in vWF-cleaving Protease Activity Associated with Increased Shear-induced Platelet Aggregation in Thrombotic Microangiopathy - Ajzenberg, Nadine; Denis, Cécile V.; Veyradier, Agnès; Girma, Jean-Pierre; Meyer, Dominique; Baruch, Dominique (Thrombosis and Haemostasis, 2002)
Von Willebrand factor (vWF) cleaving metalloprotease activity represents an important factor in understanding the pathophysiology of thrombotic microangiopathies (TMA). Thrombotic events, leading to dramatic complications, occur preferentially in the microvasculature. Our aim was to determine the ability of TMA plasma with a complete deficiency of protease activity to promote shear-induced platelet aggregation (SIPA) at high shear rates using a coaxial cylinder shearing device. We have demonstrated the ability of four out of seven TMA plasma to aggregate normal washed platelets at 4,000 s−1. In these four TMA plasma, significant SIPA was obtained, whereas control plasma did not induce more SIPA than buffer. The % of unusually large (UL) multimers in TMA plasma varied from 1 to 18%. Surprisingly, the extent of SIPA in TMA plasma appeared independent of the percentage of UL multimers. Interestingly, anti-GPIb antibody 6D1 could block completely this pathological aggregation, opening new therapeutic possibilities. In contrast, none of eight other TMA patients’ plasma with a normal protease activity, exhibited any increase of SIPA compared with control plasma. These results strongly suggest that the deficiency of vWF-cleaving protease appears to be necessary, but not sufficient for elevated SIPA. In contrast, the % of UL is not associated with increased SIPA.
Keywords: Platelet; von Willebrand factor; thrombotic thrombocytopenic purpura; metalloprotease